Seismic performance of Chilean concentrically braced frame industrial structures: effects of recent code modifications - Riquelme, Roberto; Herrera, Ricardo (Frontiers in Built Environment, 2023)
Few seismic design codes for industrial structures exist in the world. Among them, the Chilean design code was put to the test by the Maule earthquake of 2010, one of the largest seismic events in recent years. Although the seismic performance of industrial steel structures designed under these provisions was satisfactory, the standard entered a revision process based on the accumulated evidence on the performance after the event and the advances in seismic design since the code was released in 2003. The revision process led to a number of modifications to the provisions, including those for structures based on concentrically braced frames (CBF), a structural typology widely used in the industry. The modifications, mainly aimed at improving seismic performance in severe events, ranged from the seismic demand to the provisions for sizing structural elements and connections. This work evaluates the effect of these modifications on the design and seismic performance of CBFs. For this purpose, six industrial steel structures are designed using the current standards and the proposed version. The performance is evaluated through static nonlinear analyses in 3D models according to the methodology prescribed by the FEMA P695 standard (FEMAP695, 2009). The models include the nonlinearity of braces, columns, beams or struts, and anchor bolts. The results show similar performance between the structures designed using the proposed and the current version of the standard, in terms of overstrength and response modification factor. However, the performance is improved when comparing the maximum drift that the structures can reach and the energy levels, they are able to accumulate at these drifts. In terms of cost-performance ratio, the improvement in performance is associated with moderate increases in cost.